Correlational Analysis of Academic Motivational and Amotivational Approach among Education Students during Covid-19 Pandemic - Aquino, Agnes Marquez (STAI Miftahul Ula Nganjuk, 2023)
This research aims to determine the motivation of the students to study in the College and if the recent Covid-19 social distancing measures motivate them to continue. This study will also measure the amotivation level of the respondents in relation to Covid-19 pandemic learning experiences. Using descriptive correlational design which involves the systematic investigation of the nature of relationships between and among variables, the relationships of profile, academic motivation and amotivation of the respondents were explored. Following the analysis of data, respondents agreed about their motivation preference since the Covid-19 social distancing measures were put in place. Almost half of the respondents support the feelings of competence such as more teacher/student engagement, face-to-face meetings and provide action plans for academic future. Additionally, The respondents had academic motivational in terms of Striving for Excellence, Desire to Learn, and Personal Incentives. However, the respondents still experienced amotivation prior to Covid-19 pandemic. With this in line, the respondents are recommended to be given with sharing and learning activities to help them improve significantly their well-being regarding motivation to success in education.